2015
DOI: 10.1002/elan.201500466
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Lead Determination in Aviation Fuel Samples Using a Screen‐Printed Gold Electrode and Batch‐Injection Analysis

Abstract: This work presents the lead determination in aviation (bio)fuels using disposable screen‐printed gold electrodes (SPGEs) adapted on a batch‐injection cell associated with a micropipette for portable analysis. The method involves injections of 200 µL of sample or standard solutions at controlled dispensing rate (4.8 µL s−1) during deposition step (−550 mV for 90 s), followed by anodic‐stripping voltammetry. Either samples treated by sonication or dry‐ashing can be analyzed with detection limits of 0.0071 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…Polyester SPGE 0.06 0.08 0.05 4 [29] Pb 2 + Cu 2 + Hg(II) Biodiesel AuSPE 0.005 0.008 0.003 30 [82] Ciprofloxacin PF SPE modified with MWCNT 0.06 130 [83] Sildenafil PF SPE modified with GR 0.05 115 [84] Hg 2 + Biodiesel AuSPE 0.02 NR [85] Pb 2 + Aviation Fuel AuSPE 0.004 NR [86] Omeprazole PF SPE modified with MWCNT 0.009 120 [87] Corrosion inhibitors Ethanol, seawater and mineral oil SPGE 0.3 180 [88] Levamisole Levothyroxine PF SPCE or SPE modified with MWCNT Organic-resistant SPGE 0.14 0.10 170 150 [89] Nitrite Uric Acid Saliva, urine, and blood SPE modified with MWCNT 0.06 0.05 160 [90] Antioxidant capacity (DPPH) Edible oil Polyester SPGE 1.0 180 [91] [a] AF: analytical frequency (injections h À 1 ); LOD: limit of detection; PF: pharmaceutical formulation; PB: Prussian blue; GR: graphene; WE: working electrode. and selectivity) combine more with the characteristics of BIA systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyester SPGE 0.06 0.08 0.05 4 [29] Pb 2 + Cu 2 + Hg(II) Biodiesel AuSPE 0.005 0.008 0.003 30 [82] Ciprofloxacin PF SPE modified with MWCNT 0.06 130 [83] Sildenafil PF SPE modified with GR 0.05 115 [84] Hg 2 + Biodiesel AuSPE 0.02 NR [85] Pb 2 + Aviation Fuel AuSPE 0.004 NR [86] Omeprazole PF SPE modified with MWCNT 0.009 120 [87] Corrosion inhibitors Ethanol, seawater and mineral oil SPGE 0.3 180 [88] Levamisole Levothyroxine PF SPCE or SPE modified with MWCNT Organic-resistant SPGE 0.14 0.10 170 150 [89] Nitrite Uric Acid Saliva, urine, and blood SPE modified with MWCNT 0.06 0.05 160 [90] Antioxidant capacity (DPPH) Edible oil Polyester SPGE 1.0 180 [91] [a] AF: analytical frequency (injections h À 1 ); LOD: limit of detection; PF: pharmaceutical formulation; PB: Prussian blue; GR: graphene; WE: working electrode. and selectivity) combine more with the characteristics of BIA systems.…”
Section: Discussionmentioning
confidence: 99%
“…The attractive features of the BIASPE system were also explored for the on-site determination of carbendazim, catechol and hydroquinone in tap water, [20] metals (Zn 2 + , Cd 2 + , Pb 2 + , Cu 2 + , and Hg 2 + ) in biodiesel samples, [85] glucose in artificial serum sample, [21] antioxidant 2,6-di-tert-butylphenol (2, in biodiesel and jet-fuel using hydro-organic media as the supporting electrolyte, [26] lead in aviation fuel samples, [86] omeprazole in pharmaceutical samples, [87] corrosion inhibitors (2,5-dimercapto-1,3,5-thiadiazole) in fuel ethanol, seawater and mineral oil samples, [88] levamisole and sodium levothyroxine in pharmaceutical samples, [89] nitrite and uric acid in biological fluids (urine, plasma, saliva, and serum), [90] antioxidant capacity of edible oil samples, [91] benzocaine and tricaine in fish fillets, [92] and a robust electroanalytical system for detection of UVinduced DNA degradation. [93] Recently, Mendonça et al [94] reported a low-cost mechanized system fabricated using fused deposition modelling 3D-printing technology to perform injections on an electrochemical cell in wall-jet configuration (similar to a common BIA cell).…”
Section: -Nitro-p-phenylenediaminementioning
confidence: 99%
“…116 A similar study provided great promises for lead trace quantification in aviation (bio)fuel samples using SPAuE associated with anodic stripping voltammetry. 117 The continuous monitoring of a corrosion inhibitor was also demonstrated for ethanol, seawater, and mineral oil with rapid (180 analysis h −1 ) and precise (RSD < 3%) response, with a low LOD (0.3 μmol L −1 ) related to the analyses. 118 Amperometry has been utilized as the main detection method associated with BIA-SPE.…”
Section: Batch Injection Analysis (Bia)mentioning
confidence: 95%
“…Neste estudo, o pH da solução da amostra (1,4) foi ajustado para pH 2 com NaOH (1 mol.L -1 ), tendo em vista que a amostra, após a digestão, apresentou um pH muito baixo impossibilitando a determinação do íon cobre pela técnica VRA. O efeito da concentração sobre a corrente de pico mostrou uma relação linear no intervalo de 1x10 1 , com um coeficiente de correlação de 0,999.…”
Section: Parâmetros De Otimização Para Determinação Dos Metais Cobre Chumbo Níquel E Cobalto Em Amostra Digerida (Gasolinaunclassified
“…A Figura 2 mostra os voltamogramas e a respectiva curva de adição padrão para a determinação voltamétric Gasolina Comum, onde se pode ver uma excelente performance em termos de resolução dos voltamogramas e sensibilidade (coeficientes angulares) das medidas. Neste estudo, o pH da solução da amostra (1,4) foi ajustado para pH 2 com NaOH vista que a amostra, após a digestão, apresentou um pH muito baixo impossibilitando a determinação do íon cobre pela técnica VRA. O efeito da concentração sobre a corrente de pico mostrou uma relação linear no intervalo de 1x10 -7 mol.L -1 a3x10 -7 mol.Lcom um coeficiente de correlação de 0,999.…”
Section: Figura 1: (A): Resposta Voltamétrica De Cu (Ii) Em Amostra De Gasolina Comum (Amostra Digerida-nítrico-clorídrico) Em Diferentesunclassified